Survey on Handover techniques in VANETs - Thakur, Poonam; Ganpati, Anita (International Journal of Computer Sciences and Engineering, 2019)
The ITS (intelligent transport system) is working on designing intelligent vehicles with the help of Vehicular Adhoc Networks (VANETs). The motivation behind the VANETs is to provide a safe journey to the passenger by avoiding hazardous situations on the road like accidents and to provide communication between the vehicles on the move in order to transfer different types of messages, be it emergency or infotainment messages. VANETs consists of V2V (vehicle-to-vehicle), V2I (vehicle-to-infrastructure) and hybrid communication with unique features like Rapidly Changing Network Topology, Unbounded Network Size, Delay-sensitive Data Exchange, Potential Support from Infrastructure which makes it different from the other adhoc networks like MANETs. Due to these features the routing protocols used for other adhoc networks cannot be directly used for VANETs. Various new modified routing protocols are designed for VANETs. In this paper we will be discussing a little about the routing protocols for VANETs, covering almost all the major protocols being used in VANETs. The major issue which we are dealing in this paper is handover. Handover is a technique for mobility management in fast changing VANET which makes it important topic for research, since mobility management is always been a major issue in adhoc networks. There is a good amount of research information available on the mobility management for adhoc networks and for VANETs but we have not found much information about handover in VANETs. So in this paper, we have discussed about different handover techniques used for VANETs and improvements in those techniques from time to time. We have covered almost all the handover strategies and improvements made in them in the past one decade. We have represented all the handover techniques in a tabular form based on the different characteristics and features. In the end we have also given the scope which will help future researchers in their research. The paper is going to be a help to the researchers new in the field.